Pemanfaatan IT dalam Organisasi Pelajar NU di Banyuurip Ujungpangkah Gresik - Fahmul Hikam; Esa Nur Faizah; khusnul isma; Silvinatin Al Masithoh (STIT Al - Ibrohimy Bangkalan, 2024)
Advancements in information technology (IT) offer significant opportunities to enhance the efficiency and productivity of organizations, including the Nahdlatul Ulama student organization (IPNU-IPPNU) in Banyuurip Village, Ujungpangkah, Gresik. However, this organization faces challenges such as low digital literacy and minimal use of technology in its operations. This community service program aims to improve the digital competence of IPNU-IPPNU members through training on IT utilization, including Google Workspace, Canva, and social media, to support organizational administration, promotion, and communication. The methodology employed includes needs assessment, training, mentoring, and evaluation. The results indicate significant improvements in participants’ digital literacy, organizational administrative efficiency, and the quality of promotion through social media. Furthermore, participants were able to produce engaging digital content, increasing public involvement in the organization’s programs. Challenges such as limited devices and internet access were addressed through alternative solutions. This program contributes to developing NU’s youth into individuals who are not only knowledgeable in religion but also competent in information technology to face the challenges of the digital era.